Anticancer activity mechanism of novelly synthesized and characterized benzofuran ring-linked 3-nitrophenyl chalcone derivative on colon cancer cells - Oztepe, Melih; Coskun, Demet; Ari, Ferda (De Gruyter Poland Sp Z O O, 2025)
Cancer is the second biggest cause of death after cardiovascular disorders and its incidence is rising significantly. One out of every ten cancer-related deaths is caused by colon cancer. The increasing incidence calls for creating focused therapeutic strategies with fewer adverse effects than traditional clinical techniques like radiation, chemotherapy, and immunotherapy. In this study, we evaluated the anticancer effects and mechanisms of a synthesized and characterized benzofuran ring-linked 3-nitrophenyl chalcone derivative, [1-(2-benzofuranyl)-3-(3-nitrophenyl)-2-propen-1-one], on colon cancer cells (HCT-116 and HT-29) as well as healthy colon cells (CCD-18Co). Cell viability analyses using the sulforhodamine B assay demonstrated that the IC50 values after 48 h of treatment were 1.71 mu M for HCT-116, 7.76 mu M for HT-29, and higher than 10 mu M for CCD-18Co cells. These results indicate a selective cytotoxic effect on cancer cells an essential criterion for evaluating anticancer compounds. Triple fluorescence staining, flow cytometry caspase 3/7 activity, along with protein expression analyses, confirmed that the compound induces apoptosis in both cancer cell lines. At IC50 values, the derivative activated DR-4-mediated apoptosis at the membrane and BCL-2-mediated apoptosis intracellularly. Moreover, treatment with 12.5 mu M of the compound for 24 h, corresponding to a cell cycle time, statistically significantly arrested the cell cycle at the G0/G1 phase. In addition, it inhibited cell migration and colony formation in a dose-dependent manner, starting from values as low as 1.56 mu M. Additionally, the binding affinity of the derivative with target proteins was determined using artificial intelligence-assisted molecular modeling analysis. Collectively, these findings highlight the potential of this 3-nitrophenyl chalcone derivative as a promising candidate for the development of novel therapeutic agents against colon cancer.
Keywords: apoptosis; cancer; chalcone; colon; cytotoxicity